The Learning Process of Islamic Education to Foster Students' Critical Reasoning at Madrasah Ibtidaiyah Teluk Panji, North Sumatra - Desi Asmarita; Andi Prastowo (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2023)
Critical thinking is often reserved for adults. In fact, critical reasoning should have been cultivated from an early age. The importance of fostering students' critical reasoning is a demand for teachers to continue to strive for it through the learning process. Critical reasoning does not just grow, but is formed from a complex process consisting of elements that can be implemented by referring to the theory of constructivism. The learning process can be implemented by referring to the appropriate theory so that the learning process takes place with activities that will foster students' critical reasoning. So it is important to study the learning process that can foster critical reasoning. The purpose of this article is to describe the learning process of PAI to foster students' critical reasoning in madrasah ibtidaiyah. The location of this research was MIS Al-Hidayah Teluk Panji class 1. The method in this research is descriptive qualitative. Data collection was carried out using interview and documentation techniques. Furthermore, the data were analyzed descriptively.The findings in this study are that there are several stages in PAI learning to foster critical reasoning of grade 1 students, starting from making learning designs to foster critical reasoning, learning processes to evaluations oriented to active learning models. The PAI learning process to foster critical reasoning is carried out through interpretation, analysis, evaluation, inference, and self-regulation activities. Each of these activities influences the thinking ability of students through teacher guidance. The implication of this research is that PAI teachers can foster participants' critical reasoning in the learning process by taking the stages of activities according to the theory of critical thinking.